Analysis Of The Influence Of Interest Rate Savings And Other Factors On Term Saving Of Commercial Banks (Empirical Data 1990-2019) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to examine and analyze the effect of interest rate, inflation, exchange rate, and GDP per capita to time deposits at commercial banks in Indonesia using time series research data from 1990 to 2019, both short-term equilibrium relationship and long-term equilibrium relationship. The analytical method used in this research is to use the multiple linear regression method is the ordinary least squares (OLS). The results of this study indicate that there is a significant long-term equilibrium relationship between inflation and GDP on time-saving. However, in the interest rate and exchange rate variables, there is no long-term equilibrium relationship or no significant effect on time-saving. Meanwhile, the simultaneous (simultaneous) relationship or model test between the four independent variables (interest rate, exchange rate, inflation, and GDP) and the dependent variable (time-saving) in the research model is very influential (significant). The results of the error correction model (ECM) test, which is to test the short-term equilibrium relationship, show that all independent variables (interest rate, exchange rate, inflation, and GDP) do not have a short term equilibrium relationship to the dependent variable (time deposit), but simultaneously all of these independent variables affect short-term term savings.